Distribution and habitat assessment of Red Panda (Ailurus fulgens) in Kanchenjunga Conseravation Area with reference to Riya samba and Lama khanak forests - Mahato, Naveen Kumar; Karki, Jhamak Bahadur (Nepal Journal of Forestry, 2008)
A survey of red panda habitat was conducted in Kanchenjunga Conservation Area (KCA) in order to gather information regarding presence and distribution of red panda as well as its habitat condition. Secondary sources revealed the presence of red panda in 16 VDCs of Taplejung district including the four VDCs of KCA. On-sitr visit to Lelep and Wolangchung Gola VDCs revealed red panda habitat from Hellok and Lungthung up to Phalay in Lelep VDC and from Sukepani up to Jaddak and Jaritar in Wolangchung Gola VDC. Two habitats were confirmed for red panda presence through sign survey at Gyabla and Jongim, where systematic sampling on altitudinal basis was done to study the vegetation. A total of 80 plant species (25 trees, 6 shrubs, 49 herbs) and 50 species (14 trees, 8 shrubs, 28 herbs) were recorded in Gyabla and Jongim areas respectively. Abies spectabilies was the most dominant tree in both areas (IVI = 62.46 & 95.79 respectively). Both habitats were characterized by the presence of dense undergrowth of ringal bamboo (D = 204,916 & D = 42,530 stems/ha respectively). Potentialla sp., Anaphalis sp. and Plantago sp. along with the graminoides (monocot grasses) were common in both areas. Livestock grazing created disturbance to red panda, mainly during their mating season. Habitat destruction and fragmentation, people's dependency on forest for firewood and construction materials, chasing and killing of panda by the locals are the main threats to red panda in this region. Keywords: Red Panda, Habitat, Kanchenjunga Conservation Area